Little Bee - Cleave, Chris (New York : Simon & Schuster, 2009)
A haunting novel about the tenuous friendship that blooms between two disparate strangers--one an illegal Nigerian refugee, the other a recent widow from suburban London.
Includes bibliographical references.
Keywords: Young women -- Fiction; Nigerians -- England -- Fiction; Identity (Psychology) -- Fiction; Emigration and immigration -- Fiction